Reintegration of amnestied LRA ex-combatants and survivors’ resistance acts in Acholiland, Northern Uganda - Akello, Grace (International journal of transitional justice)
This article examines the social dynamics among survivors and amnestied Lord’s Resistance Army (LRA) ex-combatants living together in Acholiland, asking how and if Acholi survivors have forgiven Acholi LRA returnees, forgotten past violence and moved on, as stated in northern Uganda’s amnesty framework. The amnestied LRA ex-combatants interviewed stated that they wanted and needed to reintegrate among Acholi survivors. Yet, after two decades of amnesty, the magnitude of the brutality of the war remains etched in survivors’ minds. My ethnographic findings suggest feigned compliance as well as resistance to amnesty by-laws. Many practise what I call survivors’ acts of resistance, which includes name calling, attributing misfortune to the presence of ex-combatants, stigmatization and stealing. In short, survivors make returnees’ lives unbearable. My analysis is framed in reference to and critique of conventional transitional justice mechanisms and I underscore the importance of memory in the cessation of war violence and the restoration of peace.